Learning English as a Strategic Tool for Emerging Content Creators in the Digital Era - Af’ida ulil maghfiroh; Ahmad faruk (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores how English language skills are used as a strategic tool by beginner content creators in the digital era, particularly in the Banyuwangi region. Using a qualitative approach and case study design, the research involved ten content creators from platforms such as YouTube, Instagram, and TikTok. Data were collected through interviews, observations, and documentation. The results show that although most participants have basic to intermediate English proficiency, they still use English for writing captions, video descriptions, and engaging with global audiences. The main challenges they face include limited vocabulary, grammatical difficulties, and low self-confidence. Despite these barriers, they show strong motivation to learn and express the need for more relevant and practical English training. This study contributes by providing a clearer picture of how English proficiency can support the professional growth of local content creators and act as a bridge to wider global opportunities. It also highlights the importance of contextual and need-based English education that aligns with the realities of the digital content industry.